Oil discoveries and protectionism: role of news effects - Fidel Sebastian-Perez; Ohad Raveh; Rick van der Ploeg (Tinbergen Institute, 2021)
Can oil discovery shocks affect the demand for protectionism? An intertemporal model of Dutch disease indicates that if the tradable sector is politically dominant then an oil discovery can induce protectionism. If the economy is also credit constrained, this effect is intensified upon discovery, but partially reversed when oil revenues start to flow. We test these predictions using 16.2 million, HS-6 level, bilateral tariff rates that cover 5,718 products in 155 countries over the period 1988-2012, and data on worldwide discoveries of giant oil and gas fields. Our identification strategy rests on the exogeneity of the timing of discoveries. Our empirical results indicate that an oil discovery increases tariffs during pre-production years and decreases tariffs in the years to follow yet to a lesser extent, most notably in capital scarce economies with a relatively dominant tradable sector. Our baseline estimates indicate that a giant oil field discovery induces a rise of approximately 13% in the average tariff over the course of 10 years; this increase is approximately 2.5 times larger during the pre-production period when the oil discovery represents a pure news shock.
Keywords: Q32; F13; O24; 330; Oil discoveries; protectionism; capital scarcity; Dutch disease; political economy; trade policy; news shocks